PENENTUAN JURUSAN SISWA SEKOLAH MENENGAH ATAS DISESUAIKAN DENGAN MINAT SISWA MENGGUNAKAN ALGORITMA FUZZY C-MEANS - Altanova Reza; Abdul Syukur; Moch Arief Soeleman (Program Pascasarjana Magister Teknik Informatika, Universitas Dian Nuswantoro, 2017)
Majors are held no valid high school in Indonesia is conducted when students are still in grade X. This includes the areas of interest Majors Natural Sciences, Social Sciences, and science of language. Majors will depend on the capability of student achievement in the areas of interest / courses available and in accordance with the conditions at the school. If it is not possible then the only department of particular interest are provided in school. The results of tests that tested students' interest through psychological tests aimed to help the school and the students themselves so that later, the lessons will be given to students become more focused as it has in accordance with the capability in the field of interest. Fuzzy C-Means algorithm is an algorithm that is easy and is often used in the technique of grouping the data as it makes an estimate efficient and does not require a lot of parameters. Several studies have concluded that the Fuzzy C-Means algorithm can be used to classify data based on certain attributes. In this study will be used Fuzzy C-Means algorithm to classify the student data High School (SMA) based on the value of the core subjects for the majors that are appropriated to the interests test results. The study also examined the level of accuracy of Fuzzy C-Means algorithm in determining the majors in high school. Application of Fuzzy C-Means algorithm in determining the majors in the 278 high school students were tested in this study, indicating that the FCM algorithm has a good degree of accuracy (in an average of 82.01%) by including interest test scores compared with the manual method based on the selection of individual students only 63.67%.